Psychometric properties of the Persian social media intrusion questionnaire - Abedi, Zahra; Ashouri, Ahmad; Ramezani Farani, Abbas; Farahani, Hojjatollah (Frontiers in Psychology, 2023)
In recent years, social media use has dramatically increased worldwide, which has raised many concerns concerning the excessive use of social media. In this regard, Facebook Intrusion Questionnaire (FIQ) was developed to assess the level of addiction to Facebook. In this study, we first modified the FIQ items to cover all social media besides Facebook and labeled it the measure as Social Media Intrusion Questionnaire (SMIQ). Then, we examined its factor structure, reliability, and validity with 374 participants (M age = 25.91; SD = 5.81; 69.80% females) from the Iranian community sample. Confirmatory factor analysis supported the originally proposed uni-factor model, which was also invariant across gender groups. The SMIQ score demonstrated acceptable internal consistency (α = .85) and yielded expected associations with external correlates (e.g., cell-phone based addiction to social media, depression, and low self-esteem), supporting the measure's convergent and divergent validity. Overall, our findings indicated that Persian SMIQ enjoys sound psychometric properties.